Sistem Informasi Pemberkasan Perkuliahan Berbasis Web Menggunakan Framework Laravel - Dicky Kurniawan AM; Febi Eka Febriansyah; Rizky Prabowo; Dwi Sakethi (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2019)
Every institute, office or college must have filing activities in its business process. One of the lecture filing activities at the college is the preparation of lecture devices. The lecture device is very important and becomes a reference in every learning of a course. Nowadays, the preparation of lecture devices is still done manually and lecture filing activities will be a problem if there is no system that handles these activities, one of which is data search and storage space. The lecture filing information system has been developed to assist in the preparation and search for lecture devices. This information system was developed with Waterfall methods and Laravel framework. The conclusion of this research is the lecture filing information system is successfully built and can be used to help the preparation and search activities of lecture devices.